Rethinking Global Value Chains in Latin America under COVID 19: Challenges and Opportunities for Exporting Firms (2022)
This article examines the debate regarding regional integration and Global Value Chains (GVCs) in Latin America, and the challenges and opportunities that a deepening integration would have for exporting firms. The Latin American region had been progressively taking part in these integrated economic systems when COVID 19 hit. The pandemic has exposed weaknesses in its participation due to several factors, including its dependence on extra-regional hubs. Nevertheless, the disruption has brought back the need to consider the advantages of Latin American GVCs that could enhance the resilience and performance of regional firms. The review shows various benefits in carrying out a regional integration that is GVCs-oriented, similar to Asian and European countries. However, achieving the same level of regional GVC is not without challenges for firms, governments, and institutions. This article examines these alternatives in the context of an economic and health crisis.